Supraclavicular and/or celiac lymph node metastases from thoracic esophageal squamous cell carcinoma did not compromise survival following neoadjuvant chemoradiotherapy and surgery - Cho, Won Kyung (Oncotarget, 2016)
This study is to evaluate the prognostic significance of supraclavicular and/or celiac lymph node (LN) metastases in locally advanced thoracic esophageal squamous cell carcinoma (ESCC) patients treated with neoadjuvant chemoradiotherapy (NACRT) and surgery. Among the total 199 patients, 75 (37.7%) had supraclavicular and/or celiac LN metastasis. Surgery was performed following NACRT in 168 patients (84.4%). After the median 18.7 (1.0-147.2) months’ follow-up, 2-year rates of progression-free survival (PFS) and overall survival (OS) in all patients were 48.1% and 65.7%, respectively. In multivariate analyses, negative surgical margin (p < 0.001), ypT0 stage (p = 0.004), and ypN0 stage (p = 0.020) were significantly favorable factors for PFS, and negative surgical margin (p < 0.001) was the only significantly favorable factor for OS. Metastasis to the supraclavicular and/or celiac LNs was significant factor neither for PFS (p = 0.311) nor OS (p = 0.515). Supraclavicular and/or celiac LN metastasis did not compromise the clinical outcomes following NACRT and surgery.